Obstructive jaundice due to forgotten biliary stent- a rare case report - Deolekar, Sandesh; Mahapatra, Bibekananda; Murali, Sridevi; Ali, Sheena; Chheda, Karna; Khan, Naseem (International Journal of Research in Medical Sciences, 2017)
There are many studies about the biliary stents, however there is a little information about the long-term complications of forgotten biliary stents except a few case reports. We present a 68-years-old female patient who presented with abdominal pain, vomiting and jaundice. The patient had had a biliary prosthesis inserted 114 months (9.5 years) earlier for treatment of multiple common bile duct calculi, post cholecystectomy done in 1993. Imaging investigations evidenced the presence of obstructive jaundice and the biliary stent with gall stones adherent on its surface. After the failure of an endoscopic extraction attempt, surgical intervention ensured the removal of the stent and the gallstones formed on its surface. This case represents the rarity of such a complication after biliary stenting. At the same time, it emphasizes the need for postoperative follow-up, to avoid this kind of complication.